A comparative Proteomics Analysis Identified Differentially Expressed Proteins in Pancreatic Cancer–Associated Stellate Cell Small Extracellular Vesicles - Sarcar, Bhaswati; Fang, Bin; Izumi, Victoria; O. Nunez Lopez, Yury; Tassielli, Alexandra; Pratley, Richard; Jeong, Daniel; Permuth, Jennifer B.; Koomen, John M.; Fleming, Jason B.; Stewart, Paul A. (Molecular & cellular proteomics, 2022)
Human pancreatic stellate cells (HPSCs) are an essential stromal component and mediators of pancreatic ductal adenocarcinoma (PDAC) progression. Small extracellular vesicles (sEVs) are membrane-enclosed nanoparticles involved in cell-to-cell communications and are released from stromal cells within PDAC. A detailed comparison of sEVs from normal pancreatic stellate cells (HPaStec) and from PDAC-associated stellate cells (HPSCs) remains a gap in our current knowledge regarding stellate cells and PDAC. We hypothesized there would be differences in sEVs secretion and protein expression that might contribute to PDAC biology. To test this hypothesis, we isolated sEVs using ultracentrifugation followed by characterization by electron microscopy and Nanoparticle Tracking Analysis. We report here our initial observations. First, HPSC cells derived from PDAC tumors secrete a higher volume of sEVs when compared to normal pancreatic stellate cells (HPaStec). Although our data revealed that both normal and tumor-derived sEVs demonstrated no significant biological effect on cancer cells, we observed efficient uptake of sEVs by both normal and cancer epithelial cells. Additionally, intact membrane-associated proteins on sEVs were essential for efficient uptake. We then compared sEV proteins isolated from HPSCs and HPaStecs cells using liquid chromatography–tandem mass spectrometry. Most of the 1481 protein groups identified were shared with the exosome database, ExoCarta. Eighty-seven protein groups were differentially expressed (selected by 2-fold difference and adjusted p value ≤0.05) between HPSC and HPaStec sEVs. Of note, HPSC sEVs contained dramatically more CSE1L (chromosome segregation 1–like protein), a described marker of poor prognosis in patients with pancreatic cancer. Based on our results, we have demonstrated unique populations of sEVs originating from stromal cells with PDAC and suggest that these are significant to cancer biology. Further studies should be undertaken to gain a deeper understanding that could drive novel therapy. [Display omitted] •PDAC-associated stellate cells secrete more sEVs compared to normal stellate cells.•sEVs reduced α-SMA expressions in normal stellate cells.•Membrane proteins are essential for stellate cell sEVs uptake by normal and cancer cells.•LC-MS/MS revealed differentially expressed proteins between HPSC and HPaStec sEVs.•sEVs could be potentially targeted as cargo vehicles for the safe drug delivery. In this article, we report that cancer-associated HPSC cells secreted more sEVs than primary stellate cells (HPaStec) and had no significant growth effects on the cancer cells. Intact membrane-associated proteins may be essential for sufficient uptake of sEVs by both normal and cancer cells. Comparative proteomics analysis between the 2 different sEVs revealed differentially expressed proteins. sEVs could potentially be targeted as a cargo vehicle for the safe delivery of drugs or other biological materials to the cancer cells.